(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Employee engagement activities mostly affect the employees’ satisfaction and efficiency at work. It also resolves problems encountered by the management and its suggested improvement and solutions. The study mainly focuses on the degree of relationship between employee engagement and performance of the faculty members from the selected six (6) State Universities and Colleges (SUCs) in the National Capital Region. The researcher identifies the following gap of this study: there is limited studies found by the researcher related to faculty members, State Universities and Colleges, and sector and industry of the study; there is insufficient studies and researchers pertaining to significant differences of faculty’s profile and performance; and there is also lack of understanding about the importance of employee engagement programs in the academic sector. The survey instrument underwent an ethical assessment through the University Ethical Board of Polytechnic University of the Philippines. The study used the descriptive method of research to fulfill the objective of this study. To get the relevant data needed, the researcher utilized a survey questionnaire. There were 353 faculty members who participated in the survey. To interpret and analyze the data collected, the researcher used Frequency Distribution, Percentage, Weighted Mean, Pearson R Correlation, Estimation of Parameters, t-test, F-test, Analysis of Variance and Scheffe test. The finding shows that there are opportunities for the institutions to improve their communication, professional and personal growth, mentoring and coaching, and rewards and recognition for their faculty members. The researcher suggests that the state higher education officials and administrators should be encouraged to create more employee engagement activities to increase morale and motivate their faculty members.